Strategi Diversifikasi Usaha Perikanan untuk Meningkatkan Kesejahteraan Masyarakat Pesisir (Universitas Teknologi Muhammadiyah Jakarta (UTM Jakarta), 2025)
The diversification of fisheries businesses represents a vital strategy for improving the welfare of coastal communities. This study aims to analyze innovative and sustainable models of fisheries business diversification using a descriptive qualitative approach. The findings indicate that resource-based and technology-driven business diversification enhances the income and economic resilience of coastal communities. Several identified obstacles include capital constraints, limited market access, and a lack of technical skills. Proposed solutions encompass training programs, industry partnerships, and the formulation of policies that support community-based fisheries enterprises. Furthermore, the results demonstrate that business diversification based on marine product processing technology, aquaculture, and ecotourism is proven to effectively elevate income and bolster the economic stability of coastal populations.